Good Environmental Governance Mainstreaming in Preparation for the Implementation of Carbon Trading in Indonesia - Faradila, Novia; Aqilla, Dewi Shafarhunny (Faculty of Law Universitas Negeri Semarang, 2022)
Climate change is a global problem that is often echoed. Indonesia has an obligation to reduce greenhouse gas emissions by 29%-41% in accordance with Indonesia's commitment in the Nationally Determined Contribution (NDC). The Government's initiative in reducing Indonesia's greenhouse gas emissions was then demonstrated by issuing Presidential Regulation Number 98 of 2021 which regulates the implementation of carbon economic values carried out through mitigation and adaptation efforts. One of the steps mentioned as mitigation and adaptation efforts is carbon trading. Carbon trading is the answer to the conflicting interests of pursuing a reduction in greenhouse gas emission targets as well as increasing economic growth in Indonesia. This is supported by the existence of several factors that make carbon trading a great potential in Indonesia, including economic factors, environmental factors, and legal factors. This research is a normative juridical research and uses non-interactive qualitative research methods. In this study it was found that using the principles of Good Environmental Governance (GEG) can be a solution for the implementation of carbon trading in Indonesia later. That is by using the GEG principles which include participation, accountability, transparency, rule of law, and effectiveness and efficiency. With the implementation of this principle, the Government should immediately prepare itself carefully. Furthermore, the implementation of GEG needs to be supported by strong political will. Thus, carbon trading can be carried out optimally and bring benefits to all Indonesian people